Polypropylene Polyethylene Blend Upgrading

By using a heterogeneous copolymer as a compatibilizer, the mechanical properties of the mixture of polypropylene and polyethylene are improved, and the performance problem of difficulty in improving the recovery of polyolefin materials under a small amount of compatibilizer in the prior art is solved, and significant improvements in elongation at break and puncture resistance are achieved.

CN115916852BActive Publication Date: 2025-02-28BOREALIS AG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180047391.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-07
Filing Date
2021-07-05
Publication Date
2025-02-28
Estimated Expiration
2041-07-05

AI Technical Summary

Technical Problem

The prior art is difficult to effectively upgrade the mixture of polypropylene and polyethylene, especially in recycled materials, to improve mechanical properties such as elongation of break, impact strength and puncture resistance under small amounts of compatibilizers.

Method used

As the compatibilizer, a heterophase copolymer containing a matrix phase and an elastomeric phase dispersed therein is used, and the matrix phase contains a random polypropylene copolymer with specific melt flow rate, melting point range and xylene dissolution characteristics.

Benefits of technology

By using this compatibilizer, the elongation of breakage, impact strength of the simply supported beam notched and puncture resistance of the polypropylene-polyethylene blend can be significantly improved, especially under low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004034768050000191
    Figure BDA0004034768050000191
  • Figure BDA0004034768050000201
    Figure BDA0004034768050000201
  • Figure BDA0004034768050000211
    Figure BDA0004034768050000211
Patent Text Reader

Abstract

Use of a compatibilizer (B) for upgrading a polypropylene-polyethylene blend (A), the polypropylene-polyethylene blend (A) comprising (A-1) polypropylene and (A-2) polyethylene, wherein the weight ratio of polypropylene (A-1) to polyethylene (A-2) is in the range of 19:1 to 1:19, the upgrading being with respect to at least one or more of the following properties: (i) elongation at break (ISO 527-1,2; F3 / 4), (ii) notched charpy impact strength (1eA) (non-instrumented, ISO 179-1, +23°C); (iii) notched charpy impact strength (1eA) (non-instrumented, ISO 179-1, 0°C); (iv) notched charpy impact strength (1eA) (non-instrumented, ISO 179-1, -20°C); (v) puncture resistance (energy, ISO7785-2, +23°C), and (vi) low temperature puncture resistance (energy, ISO 7765-2, 0°C or -20°C), wherein the amount of compatibilizer (B) is 1 to 35% by weight, preferably 2 to 25% by weight, and more preferably 3 to 9% by weight relative to the final composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to heterophasic polymers suitable for upgrading blends of polypropylene and polyethylene, in particular for upcycling polyolefin materials, and the use of such heterophasic polymers for upgrading blends of polypropylene and polyethylene. The present invention also relates to upgraded polypropylene polyethylene compositions. Background Art

[0002] The characteristic of the mixture of polypropylene and polyethylene is limited miscibility. When such mixtures are processed into final products, the mechanical and optical properties limit the possible applications to ultra-low-cost applications with low requirements, such as park benches or geotextile reinforcements. The blending morphology is one of the decisive obstacles to achieving valuable applications, which is particularly evident in the field of recycled materials. A very common recycling stream contains polyethylene and polypropylene and many by-products. It can be separated using density separation in water and then further separated based on fluorescence, near-infrared absorption or Raman fluorescence. However, it is usually difficult to obtain pure recycled polypropylene or pure recycled polyethylene. Typically, a large amount of polypropylene recycled on the market is a mixture of polypropylene (PP) and polyethylene (PE), especially for post-consumer waste streams. In addition, the recycled polyolefin materials are often cross-contaminated by non-polyolefin materials such as polyethylene terephthalate, polyamide, polystyrene or non-polymeric substances such as wood, paper, glass or aluminum, further limiting the morphology. The use of various compatibilizers is known in the art. Jun Xu et al. describe the use of diblock, tetrablock and hexablock copolymers (BCP) to compatibilize isotactic polypropylene and HDPE in Macromolecules 2018, 51 (21), 8585-8596. The author also describes the use of ethylene propylene rubber (EPR) and ethylene propylene diolefin monomer (EPDM) rubber to cause phase separation problems, and when the amount used is large, the tensile strength is reduced. Olefin block copolymers (OBC) are reported to be good compatibilizers for PE and iPP mixtures, such as Munro J. et al., Proc. SPE ANTEC 2017, described in 961-966. However, due to challenging and expensive production methods, the widespread use of OBC is limited. Another group of compatibilizers is ethylene octene elastomer (EO rubber), which is also quite expensive and may reduce stiffness. The use of multiphase copolymers and multiphase random copolymers for upgrading recycled polyolefin streams has been described in the literature, which mainly relates to stiffness and impact properties. WO2007071494A1 teaches the use of heterophasic polyolefin compositions having a flexural modulus of less than 600 MPa in a wide melt flow rate range of 0.5 to 20 g / 10 min and a wide elongation at break range of 100% to 1000%. In particular, a low MFR (0.6 g / 10 min) heterophasic polyolefin "HC2" has been exemplarily used to upgrade recyclates with a PE / PP ratio of about 18, the heterophasic polyolefin "HC2" comprising two propylene copolymer fractions, a first propylene random copolymer insoluble in xylene and a substantially linear second ethylene / propylene copolymer, and an ethylene-propylene rubber with an intrinsic viscosity of 3.2 dl / g. The compatibilizer "HC2" is further visbroken to produce an MFR of 8 g / 10 min and used for recyclates with a PE / PP ratio of about 1. It has been shown that the elongation at break values ​​of the upgraded composition are only satisfactory at an undesirably high content of a high heterophasic polyolefin.

[0003] Therefore, there is a felt need in the art for further compatibilizers for PP / PE blends in order to improve the mechanical properties at low levels of compatibilizer, i.e. to improve the balance between flowability (MFR), stiffness (measured by tensile modulus ISO 1873-2), impact strength (Charpy notched impact strength ISO 179-1eA at +23°C and -20°C), in particular elongation at break (ISO 527-2) and room temperature puncture resistance (23°C), in particular cold puncture resistance (at 0°C and -20°C). Summary of the invention

[0004] The present invention provides a use of a compatibilizer (B) for upgrading a polypropylene-polyethylene blend (A), wherein the compatibilizer (B) is a heterophasic copolymer comprising a matrix phase and an elastomeric phase dispersed therein, wherein the matrix phase comprises a random polypropylene copolymer, and wherein the heterophasic copolymer has

[0005] - melt flow rate MFR2 (230°C, ISO 1133) of 2.0 to 30 g / 10 min, and

[0006] - at least one melting point Tm1 in the range of 154°C to 168°C,

[0007] - optionally a second melting point Tm2 in the range of 130°C to 160°C,

[0008] - optionally the second or third melting point Tm3 is in the range of 110°C to 125°C,

[0009] - a xylene cold insoluble content (XCI) of 60 to 80% by weight, preferably 70 to 80% by weight (ISO 16152, 1st edition, 25° C.), and

[0010] - a xylene cold soluble content (XCS) of 20 to 40 wt.-% (ISO 16152, 1st edition, 25° C.), wherein the xylene cold insoluble content (XCI) and the xylene cold soluble content (XCS) add up to 100 wt.-%,

[0011] - the content of units derived from ethylene in the xylene cold insoluble fraction (XCI) is from 2.0 to 6.0% by weight, preferably from 2.3 to 3.5% by weight, and

[0012] - the content of units derived from ethylene in the xylene cold soluble fraction (XCS) is from 20.0 to 40.0% by weight, preferably from 25.0 to 35.0% by weight;

[0013] - the xylene cold soluble fraction (XCS) has an intrinsic viscosity (measured in decalin at 135° C. according to DIN ISO 1628 / 1) of 2.1 dl / g to less than 6.0 dl / g, preferably 3.0 to 5.0 dl / g, more preferably 3.3 to 4.3 dl / g,

[0014] The polypropylene-polyethylene blend (A) comprises

[0015] (A-1) polypropylene, and

[0016] (A-2) Polyethylene

[0017] The weight ratio of polypropylene (A-1) to polyethylene (A-2) is 19:1 to 1:19,

[0018] The upgrade is related to at least one or more of the following properties:

[0019] (i) Elongation at break (ISO 527-2)

[0020] (ii) Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C);

[0021] (iii) Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +0°C);

[0022] (iv) Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, -20 °C);

[0023] (v) Puncture resistance (energy, ISO7785-2, 23°C)

[0024] (vi) Low temperature puncture resistance (energy, ISO 7765-2, 0°C or -20°C)

[0025] The amount of the compatibilizer (B) used is 1 to 35 wt %, preferably 2 to 25 wt %, more preferably 3 to 9 wt %, relative to the final composition.

[0026] The present invention also provides a method for upgrading a polypropylene-polyethylene blend (A), wherein the polypropylene-polyethylene blend (A) comprises

[0027] (A-1) polypropylene, and

[0028] (A-2) Polyethylene

[0029] The weight ratio of polypropylene (A-1) to polyethylene (A-2) is 19:1 to 1:19,

[0030] The upgrade is related to at least one or more of the following properties:

[0031] (i) Elongation at break (ISO 527-2)

[0032] (ii) Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C);

[0033] (iii) Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, 0°C);

[0034] (iv) Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, -20 °C);

[0035] (v) Puncture resistance (energy, ISO7785-2, 23°C)

[0036] (vi) Low temperature puncture resistance (energy, ISO 7765-2, 0°C or -20°C)

[0037] The method is achieved by melt blending the polypropylene-polyethylene blend (A) with a compatibilizer (B),

[0038] The amount of the compatibilizer (B) is 1 to 35 wt%, preferably 2 to 25 wt%, more preferably 3 to 9 wt%, relative to the final composition, wherein the compatibilizer (B) is a heterophasic copolymer comprising a matrix phase and an elastomeric phase dispersed therein, wherein the matrix phase comprises a random polypropylene copolymer, and wherein the heterophasic copolymer has

[0039] - melt flow rate MFR2 (230°C, ISO 1133) of 2.0 to 30 g / 10 min, and

[0040] - at least one melting point Tm1 in the range of 154°C to 168°C,

[0041] - Optionally the second melting point Tm2 is in the range of 130°C to 160°C

[0042] - optionally the second or third melting point Tm3 is in the range of 110°C to 125°C,

[0043] - a xylene cold insoluble content (XCI) of 60 to 80% by weight, preferably 70 to 80% by weight (ISO 16152, 1st edition, 25° C.), and

[0044] - a xylene cold soluble content (XCS) of 20 to 40% by weight, preferably 20 to 30% by weight (ISO 16152, 1st edition, 25° C.), wherein the xylene cold insoluble content (XCI) and the xylene cold soluble content (XCS) add up to 100% by weight,

[0045] - the content of units derived from ethylene in the xylene cold insoluble fraction (XCI) is from 2.0 to 6.0% by weight, preferably from 2.3 to 3.5% by weight, and

[0046] - the content of units derived from ethylene in the xylene cold soluble fraction (XCS) is from 20.0 to 40.0% by weight, preferably from 25.0 to 35.0% by weight;

[0047] The xylene cold soluble fraction (XCS) has an intrinsic viscosity (measured in decalin at 135° C. according to DIN ISO 1628 / 1) of 2.1 dl / g to less than 6.0 dl / g, preferably 3.0 to 5.0 dl / g, more preferably 3.3 to 4.3 dl / g.

[0048] In another aspect, the present invention provides a polypropylene-polyethylene composition obtainable by blending:

[0049] a) 65 to 99 wt. %, preferably 75 to 98 wt. %, more preferably 91 to 97 wt. % of a polypropylene-polyethylene blend (A), said polypropylene-polyethylene blend (A) comprising

[0050] A-1) Polypropylene,

[0051] A-2) Polyethylene,

[0052] The weight ratio of polypropylene to polyethylene is 19:1 to 1:19.

[0053] as well as

[0054] b) 1 to 35 wt. %, preferably 2 to 25 wt. %, more preferably 3 to 9 wt. % of a compatibilizer (B), said compatibilizer (B) being a heterophasic copolymer comprising a matrix phase and an elastomeric phase dispersed therein, wherein said matrix phase comprises a random polypropylene copolymer, and wherein

[0055] The heterophasic copolymer has

[0056] - melt flow rate MFR2 (230°C, ISO 1133) of 2.0 to 30 g / 10 min, and

[0057] - at least one melting point Tm1 in the range of 154°C to 168°C,

[0058] - Optionally the second melting point Tm2 is in the range of 130°C to 160°C

[0059] - optionally the second or third melting point Tm3 is in the range of 110°C to 125°C,

[0060] - a xylene cold insoluble content (XCI) of 60 to 80% by weight, preferably 70 to 80% by weight (ISO 16152, 1st edition, 25° C.), and

[0061] - a xylene cold soluble content (XCS) of 20.0 to 40.0% by weight, preferably 20 to 30% by weight (ISO 16152, first edition, 25° C.), wherein the xylene cold insoluble content (XCI) and the xylene cold soluble content (XCS) add up to 100% by weight,

[0062] - the content of units derived from ethylene in the xylene cold insoluble fraction (XCI) is from 2.0 to 6.0% by weight, preferably from 2.3 to 3.5% by weight, and

[0063] - the content of units derived from ethylene in the xylene cold soluble fraction (XCS) is from 20.0 to 40.0% by weight, preferably from 25.0 to 35.0% by weight;

[0064] - the xylene cold soluble fraction (XCS) has an intrinsic viscosity (measured in decalin at 135° C. according to DIN ISO 1628 / 1) of 2.1 dl / g to less than 6.0 dl / g, preferably 3.0 to 5.0 dl / g, more preferably 3.3 to 4.3 dl / g, and

[0065] - wherein the ratio MFR2(blend (A)) / MFR2(compatibilizer (B)) ((ISO 1133, 2.16 kg load, 230°C) is in the range of 0.1 to 12.5.

[0066] In another aspect, the present invention provides a heterophasic copolymer for compatibilizing polypropylene / polyethylene blends, comprising a matrix phase and an elastomeric phase dispersed therein, wherein the matrix phase comprises a random polypropylene copolymer, and wherein

[0067] The heterophasic copolymer has

[0068] - melt flow rate MFR2 (230°C, ISO 1133) of 2.0 to 30 g / 10 min, and

[0069] - at least one melting point Tm1 in the range of 154°C to 168°C,

[0070] - Optionally the second melting point Tm2 is in the range of 130°C to 160°C

[0071] - optionally the second or third melting point Tm3 is in the range of 110°C to 125°C,

[0072] - a xylene cold insoluble content (XCI) of 60 to 80% by weight, preferably 70 to 80% by weight (ISO 16152, 1st edition, 25° C.), and

[0073] - a xylene cold soluble content (XCS) of 20 to 40% by weight, preferably 20 to 30% by weight (ISO 16152, 1st edition, 25° C.), wherein the xylene cold insoluble content (XCI) and the xylene cold soluble content (XCS) add up to 100% by weight,

[0074] - the content of units derived from ethylene in the xylene cold insoluble fraction (XCI) is from 2.0 to 6.0% by weight, preferably from 2.3 to 3.5% by weight, and

[0075] - the content of units derived from ethylene in the xylene cold soluble fraction (XCS) is from 20.0 to 40.0% by weight, preferably from 25.0 to 35.0% by weight;

[0076] The xylene cold soluble fraction (XCS) has an intrinsic viscosity (measured in decalin at 135° C. according to DIN ISO 1628 / 1) of 2.1 dl / g to less than 6.0 dl / g, preferably 3.0 to 5.0 dl / g, more preferably 3.3 to 4.3 dl / g.

[0077] definition

[0078] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs. Although any methods and materials similar or equivalent to those described herein can be used in practice to test the present invention, preferred materials and methods are described herein. In describing and claiming the present invention, the following terms will be used according to the definitions listed below. Unless otherwise explicitly stated, the use of the terms "one", "a kind of", etc. refers to one or more. The propylene homopolymer-random copolymer matrix phase of the compatibilizer (B) (i.e., the multiphase copolymer according to the present invention) represents a matrix phase composed of a mixture of propylene homopolymer and random polypropylene copolymer. The presence of two polymers (i.e., the first polypropylene homopolymer and the second polypropylene random copolymer) can be detected by differential scanning calorimetry (DSC) by the presence of two melting points within a specified range, such as by two identifiable peaks, or peaks and shoulders. "Upgrade" refers to improving one or more properties, such as the elongation at break, the notched impact of the reactant mixture, or the particle morphology, so that the resulting composition (i.e., the combination of the reactant blend and the compatibilizer) exhibits one or more properties that are superior to the reactant blend. The dispersed phase particle morphology describes the size distribution of the dispersed phase particles as can be observed by microscopy. "Upgrading" of the dispersed phase particle morphology means that the morphology of the dispersed phase as observed by microscopy and optionally analyzed by image analysis methods is refined.

[0079] For the purposes of this invention, the following shall be considered “upgrades” or “improvements”:

[0080] - an increase in the elongation at break (ISO 527-2) of at least 50%, in particular 100%, relative to the initial value;

[0081] - an increase of at least 5.0%, in particular 10%, in the Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C) relative to the starting value;

[0082] - an increase of at least 5.0%, in particular 10%, in the Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, 0°C) relative to the starting value;

[0083] - an increase of at least 5.0%, in particular 10%, in the Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, -20°C) relative to the starting value;

[0084] - an increase in puncture energy (ISO 7765-2, +23°C) of at least 15% relative to the starting material;

[0085] - The puncture energy (ISO 7765-2, -20°C or 0°C) is increased by at least 15% relative to the starting material.

[0086] For the purpose of this specification, the term "recycled waste" or "recycled material" is used to refer to materials recovered from post-consumer waste and industrial waste, as opposed to virgin polymers. Post-consumer waste refers to objects that have completed at least the first use cycle (or life cycle), that is, have reached their first purpose; while industrial waste refers to manufacturing waste, which usually does not reach the hands of consumers. The term "virgin" refers to newly produced materials and / or items before their first use, which have not yet been recycled. Virgin materials and recycled materials can be easily distinguished based on the presence or absence of contaminants such as limonene and / or fatty acids and / or paper and / or wood. Polypropylene-polyethylene blends can also be distinguished from their sources by the presence of polystyrene and / or polyamide. Residual refers to the content above the detection limit. Many different types of polyethylene or polypropylene may be present in "recycled materials". The ratio of polypropylene (A-1) to polyethylene plus polyethylene copolymer (A-2) is determined experimentally by calibration using isotactic polypropylene (iPP) and high-density polyethylene (HDPE). Polymer blends are mixtures of two or more polymer components. Generally, blends can be prepared by mixing two or more polymer components. Suitable mixing steps known in the art are post-polymerization blending. Post-polymerization blending can be dry blending of polymer components such as polymer powders and / or compounded polymer pellets or melt blending of polymer components by melt mixing. Propylene random copolymers are copolymers of propylene monomer units and comonomer units, wherein the comonomer units are randomly distributed on the polypropylene chain. "Compatibilizer" is a substance in polymer chemistry that is added to polymer mixtures with limited miscibility to increase their stability. "Polypropylene-polyethylene blend" refers to a composition comprising both polypropylene and polyethylene, including polypropylene copolymers and polyethylene copolymers. Since the polypropylene content and polyethylene content cannot be directly determined, the weight ratio of polypropylene (A-1) to polyethylene (A-2) is 19:1 to 1:19, which represents an equivalent ratio determined by iPP and HDPE calibration and IR spectroscopy. The term "elastomer" refers to a natural or synthetic polymer with elastic properties. The term "XCS" refers to the xylene cold soluble content (XCS weight %) measured at 25°C according to ISO 16152. The term "XCI" refers to the xylene cold insoluble content (XCI weight %) measured at 25°C according to ISO 16152. If not otherwise specified, "%" refers to weight %. The presence of a multiphase nature can be easily determined by the number of glass transition points. Reactor blends are blends derived from production in two or more reactors connected in series or in a reactor with two or more reaction compartments. Alternatively, reaction blends can be produced by blending in solution. Reaction blends are contrasted with compounds produced by melt extrusion.

[0087] Compatibilizer

[0088] The compatibilizer according to the present invention is a heterophasic copolymer comprising a matrix phase and an elastomeric phase dispersed therein, wherein the matrix phase comprises a random polypropylene copolymer and a polypropylene homopolymer. Those skilled in the art will immediately recognize the presence of a polypropylene homopolymer, which can be easily detected by differential scanning calorimetry, for example, by melting peak analysis. In other words, the presence of at least one melting point Tm1 in the range of 154°C to 168°C indicates the presence of a polypropylene homopolymer. Typically, the heterophasic copolymers comprise a polypropylene homopolymer matrix (usually denoted as HECO), or they comprise a random polypropylene copolymer matrix (usually denoted as RAHECO), wherein such a matrix may also be composed of two random polypropylene copolymers having different molecular weight distributions and / or comonomer contents. The melt flow rate MFR2 (230°C, ISO1133) of the heterophasic copolymer according to the present invention is 2.0 to 30 g / 10 min, preferably 5.0 to 15.0 g / 10 min, and most preferably 6.0 to 15.0 g / 10 min. The heterophasic copolymer according to the invention must also have at least one melting point Tm1 in the range of 154°C to 168°C. As mentioned above, such a melting point indicates the presence of a homopolymer. Optionally, there is a second melting point Tm2 in the range of 130°C to 160°C derived from the random polypropylene copolymer. It is possible that the melting point of the random polypropylene copolymer is clearly visible in the temperature range of 130°C to 160°C. However, this is usually not the case and the melting point will appear as a shoulder in the DSC thermogram. The heterophasic copolymer according to the invention optionally has at least a second or third melting point Tm3 in the range of 110°C to 125°C. This melting point originates from polyethylene. The multiphase copolymer according to the invention must also have a xylene cold insoluble content (XCI) (ISO 16152, first edition, 25° C.) of 60 to 80 wt. %, preferably 70 to 80 wt. % and a xylene cold soluble content (XCS) (ISO 16152, first edition, 25° C.) of 20 to 40 wt. %, preferably 20 to 30 wt. %, wherein the xylene cold insoluble content (XCI) and the xylene cold soluble content (XCS) add up to 100 wt. %. The amount of the xylene cold soluble component should not be too high, as this may reduce the stiffness, and should not be too low, otherwise the impact resistance and puncture resistance may not be sufficient. The skilled person will understand that both the matrix component and the elastomer component contribute to the xylene cold soluble content. As can be seen from the experimental part, the propylene homopolymer-polypropylene random copolymer mixture (i.e. the mixture that constitutes the matrix component produced by reactors one and two) has a higher xylene cold soluble content.

[0089] The heterophasic copolymer according to the invention also has a content of units derived from ethylene in the xylene cold insoluble fraction (XCI) of 2.0 to 6.0 wt. %, preferably 2.3 to 3.5 wt. %. In addition, the content of units derived from ethylene in the xylene cold soluble fraction (XCS) of the heterophasic copolymer according to the invention is 20.0 to 40.0 wt. %, preferably 25.0 to 35.0 wt. %. On the other hand, the xylene cold soluble fraction (XCS) of the heterophasic copolymer according to the invention can have an intrinsic viscosity in a wide range of 2.1 dl / g to less than 6.0 dl / g (measured in decalin at 135 ° C according to DIN ISO 1628 / 1). Preferably, the intrinsic viscosity of the xylene cold soluble fraction (XCS) is in the range of 3.0 to 5.0 dl / g and most preferably in the range of 3.3 to 4.3 dl / g. Such an IV (XCS) range is particularly advantageous for impact resistance and puncture resistance. In yet another preferred aspect, the xylene cold soluble fraction (XCS) comprises only units derived from ethylene and propylene. That is, the elastomer can only be a copolymer of propylene and ethylene.

[0090] The heterophasic copolymer according to the present invention is preferably a reactor blend of propylene homopolymer, random polypropylene copolymer and ethylene-propylene rubber. Therefore, the heterophasic copolymer according to the present invention can be easily prepared in various types of polymer equipment, such as Configuration (loop reactor-gas phase reactor 1-gas phase reactor 2), Spheripol configuration (loop reactor 1-loop reactor 2-gas phase reactor 1), Spheripol configuration with liquid propylene as barrier gas and other common types of production units.

[0091] The heterophasic copolymer according to the present invention, ie the compatibilizer (B), preferably has a tensile modulus (measured according to ISO 527-2) of at least 625 MPa, more preferably at least 650 MPa and most preferably at least 700 MPa.

[0092] On the other hand, the heterophasic copolymer according to the invention, ie the compatibilizer (B) according to the invention, has a total content of units derived from ethylene of 6.0 to 12.0% by weight.

[0093] In a specific embodiment, the compatibilizer (B) is prepared by using a Ziegler Natta catalyst. If so, at least one melting point Tm1 in the range of 154°C to 168°C will be found in the range of 161°C to 168°C. Due to processability and cost advantages, a compatibilizer having at least one melting point Tm1 in the range of 161°C to 168°C is preferred.

[0094] Polypropylene-polyethylene blends (A)

[0095] The polypropylene-polyethylene blend (A) according to the present invention preferably has at least one or more of the following properties:

[0096] a) a limonene content of 0.1 ppm to 100 ppm, preferably 0.1 ppm to 50 ppm, more preferably 0.1 ppm to 20 ppm, most preferably 0.1 ppm to 5 ppm, as determined using solid phase microextraction (HS-SPME-GC-MS);

[0097] b) a fatty acid content of 0.1 to 100 ppm as determined using solid phase microextraction (HS-SPME-GC-MS);

[0098] c) a polyamide content of 0.05 to 1.5 wt. % as determined by NMR;

[0099] d) a polystyrene content of 0.05 to 3.0% by weight, determined by NMR.

[0100] Preferably, the polypropylene-polyethylene blend (A) according to the present invention is recycled material, more preferably originated from household waste.

[0101] The polypropylene-polyethylene blend (A) according to the present invention comprises

[0102] (A-1) polypropylene, and

[0103] (A-2) Polyethylene

[0104] The weight ratio of polypropylene (A-1) to polyethylene (A-2) is 19:1 to 1:19.

[0105] It should be understood that the composition of the polypropylene-polyethylene blend (A) can vary widely, i.e. can contain polypropylene homopolymer, polypropylene copolymer, polyethylene and polyethylene copolymer. Since the polypropylene content and polyethylene content cannot be directly determined, the weight ratio of polypropylene (A-1) to polyethylene (A-2) of 19:1 to 1:19 is an equivalent ratio determined by calibration of iPP and HDPE.

[0106] Generally, the polypropylene-polyethylene blend (A) according to the present invention may have one or more of the following properties:

[0107] - residual PET determined as described in the experimental section;

[0108] - residual talc and chalk content as described in the experimental part;

[0109] - Residual metal content (determined by X-ray fluorescence (XRF));

[0110] - the amount of residual paper as described in the experimental section;

[0111] - Amount of residual wood as described in the experimental part;

[0112] - Total free fatty acid content measured using headspace solid phase microextraction (HS-SPME-GC-MS) ranged from 0.1 to 100 ppm.

[0113] For upgrade

[0114] The compatibilizer according to the present invention is used to upgrade a polypropylene-polyethylene blend (A), wherein the polypropylene-polyethylene blend (A) comprises

[0115] (A-1) polypropylene, and

[0116] (A-2) Polyethylene

[0117] The weight ratio of polypropylene (A-1) to polyethylene (A-2) is 19:1 to 1:19.

[0118] The upgrade is related to at least one or more of the following properties:

[0119] (i) Elongation at break (ISO 527-2);

[0120] (ii) Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C);

[0121] (iii) Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, -20 °C);

[0122] (iv) a 15% increase in puncture energy (ISO 7765-2, 23°C) relative to the starting material;

[0123] (v) The low temperature puncture energy (ISO 7765-2, -20°C or 0°C) was increased by 15% relative to the starting material.

[0124] According to the invention, the amount of compatibilizer (B) used is from 1 to 35% by weight, preferably from 2 to 25% by weight, more preferably from 3 to 9% by weight, relative to the final composition. Amounts of compatibilizer greater than the specified maximum of 35% by weight, preferably 25% by weight, most preferably 9% by weight should be avoided, otherwise the elongation at break and / or the stiffness may again be impaired.

[0125] Polypropylene-polyethylene composite

[0126] Preferred aspects of the polypropylene-polyethylene composition according to the present invention are described below.

[0127] The polypropylene-polyethylene composition according to the present invention should have a relatively high stiffness. Hence, the compatibilizer (B) preferably has a tensile modulus of at least 625 MPa, more preferably at least 650 MPa and most preferably as described above.

[0128] Products

[0129] The present invention also relates to an article comprising, preferably consisting of, a polypropylene-polyethylene composition as described above. DETAILED DESCRIPTION

[0130] In a particularly preferred embodiment, the heterophasic copolymer for compatibilizing polypropylene / polyethylene blends comprises a matrix phase and an elastomeric phase dispersed therein, wherein the matrix phase comprises a random polypropylene copolymer, and wherein the heterophasic copolymer has

[0131] - melt flow rate MFR2 (230°C, ISO 1133) of 2.0 to 30 g / 10 min, and

[0132] - at least one melting point Tm1 in the range of 154°C to 168°C,

[0133] - optionally a second melting point Tm2 in the range of 130°C to 160°C,

[0134] - optionally the second or third melting point Tm3 is in the range of 110°C to 125°C,

[0135] - a xylene cold insoluble content (XCI) of 70 to 80% by weight (ISO 16152, 1st edition, 25° C.), and

[0136] - a xylene cold soluble content (XCS) of 20 to 30 wt.-% (ISO 16152, 1st edition, 25° C.), wherein the xylene cold insoluble content (XCI) and the xylene cold soluble content (XCS) add up to 100 wt.-%,

[0137] - the content of units derived from ethylene in the xylene cold insoluble fraction (XCI) is from 2.0 to 6.0% by weight, preferably from 2.3 to 3.5% by weight, and

[0138] - a content of units derived from ethylene in the xylene cold soluble fraction (XCS) of 25.0 to 35.0% by weight;

[0139] The xylene cold soluble fraction (XCS) has an intrinsic viscosity (measured in decalin at 135° C. according to DIN ISO 1628 / 1) of 3.3 to 4.3 dl / g.

[0140] The heterophasic copolymer preferably has a tensile modulus of at least 650 MPa (measured according to ISO 527-2). In another aspect, the matrix of the heterophasic copolymer comprises, preferably consists of, a polypropylene homopolymer-random polypropylene copolymer mixture. In another aspect, the xylene cold soluble component (XCS) of the heterophasic copolymer comprises only units derived from ethylene and propylene. In addition, it is also preferred that the heterophasic copolymer is a reactor blend of a propylene homopolymer, a random polypropylene copolymer and an ethylene-propylene rubber.

[0141] Two particularly preferred embodiments will be described below.

[0142] The polypropylene-polyethylene composition according to the first specific and preferred embodiment of the present invention preferably has at least one or more of the following properties:

[0143] - Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C) of at least 7.0 kJ / m 2 , and / or

[0144] - a Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, -20°C) of at least 2.5 kJ / m2, and / or

[0145] - an elongation at break (ISO 527-2) of at least 200%, in particular 300%;

[0146] - a tensile modulus of at least 800 MPa (ISO 527-2);

[0147] - puncture energy (ISO 7765-2, +23°C) of at least 4.0 J;

[0148] - The puncture energy (ISO 7765-2, -20°C) is at least 0.6 J.

[0149] At least 7.0 kJ / m can be easily achieved by using higher amounts of compatibilizer. 2 The xylene cold soluble fraction has an intrinsic viscosity IV (XCS) in the range of 3.3 to 4.3 dl / g, which is favorable for a Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, -20°C) of at least 2.5 kJ / m 2Good elongations at break (ISO 527-2) of at least 200%, in particular 300%, require limited amounts of compatibilizers and an intrinsic viscosity IV (XCS) of the xylene cold soluble fraction of preferably 3.0 to 5.0 dl / g, more preferably 3.3 to 4.3 dl / g. A tensile modulus of at least 800 MPa can only be achieved with limited amounts of compatibilizers and an optional xylene cold soluble content at the lower end of the expected range.

[0150] The blend (A), i.e. the recyclate preferably contained in this first specific and preferred embodiment, preferably has one or more of the following characteristics:

[0151] - The ratio of polypropylene to polyethylene is 2:1 to 1:2;

[0152] - a tensile modulus (ISO 527-2) of at least 900 MPa;

[0153] - Melt flow rate MFR2 (ISO 1133, 230°C, 2.16 kg)) of 3.0 to 10.0 g / 10 min.

[0154] The polypropylene-polyethylene composition according to the second specific and preferred embodiment of the present invention preferably has at least one or more of the following properties:

[0155] - a tensile modulus (ISO 527-2) of at least 1200 MPa, and / or

[0156] - Elongation at break (ISO 527-2) of at least 40%.

[0157] The blend (A), i.e. the recyclate preferably contained in this second specific and preferred embodiment, preferably has one or more of the following characteristics:

[0158] - a ratio of polypropylene to polyethylene of 19:1 to 10:1;

[0159] - a tensile modulus (ISO 527-2) of at least 1100 MPa;

[0160] - melt flow rate MFR2 (ISO1133, 230°C, 2.16 kg)) is 7.0 to 25.0 g / 10 min, preferably 7.0 to 17.0 g / 10 min.

[0161] Experimental Section

[0162] The following examples are included to demonstrate certain aspects and embodiments of the present invention as described in the claims. However, it should be understood by those skilled in the art that the following description is exemplary only and should not be construed in any way as limiting the present invention.

[0163] Test Method

[0164] a) Amount of iPP, polystyrene, polyethylene (and copolymers containing ethylene), poly(ethylene terephthalate) and amount of polyamide-6

[0165] To establish different calibration curves, different standard iPP and HDPE as well as iPP, PS and PA6 were blended. To quantify the content of foreign polymers, IR spectra were recorded in the solid state using a Bruker Vertex 70 FTIR spectrometer. Films were prepared using a compression molding device at 190 °C and a clamping force of 4 to 6 MPa. The film thickness for the calibration standards for iPP and HDPE was 300 μm, and for the quantification of iPP, PS and PA6 a film thickness of 50-100 0 μm was used. Standard transmission FTIR spectroscopy was used, which used a spectral range of 4000-400 cm -1 , aperture is 6mm, spectral resolution is 2cm -1 , 16 background scans, 16 spectral scans, interferogram zero fill factor of 32 and Norton Beer strong apodization.

[0166] Measured 1167cm in iPP -1 The absorbance of the band at was measured and the iPP content was quantified according to the calibration curve (absorption / thickness (cm) vs. iPP content (wt %)).

[0167] Measurements 1601cm -1 (PS) and 3300cm -1 The absorbance of the band at (PA6) was measured and the PS and PA6 contents were quantified according to the calibration curve (absorption / thickness (cm) vs. PS and PA6 content (wt%)). The content of polyethylene and ethylene-containing copolymers was obtained by subtracting (iPP+PS+PA6) from 100, taking into account the content of non-polymeric impurities determined in the following method. The analysis was performed as a double determination.

[0168] b) Tensile modulus and tensile strain at break

[0169] The measurements were carried out according to ISO 527-2 (crosshead speed = 1 mm / min; test speed 50 mm / min, 23°C) using injection moulded samples 1B (dog bone shape, 4 mm thickness) prepared as described in EN ISO 1873-2. The samples were measured after a conditioning time of 96 hours at 23°C.

[0170] c) Impact strength

[0171] Impact strength on 80x10x4mm prepared according to EN ISO 1873-2 3The Charpy notched impact strength was determined on injection-moulded specimens according to ISO 179-1eA at +23° C., 0° C. and −20° C. The specimens were measured after a conditioning time of 96 hours at 23° C.

[0172] d) Instrumented puncture test

[0173] According to ISO6603-2:2000, at +23℃, 0℃ and -20℃, 60x60x1 mm 3 Instrumented puncture test for injection molded plaques. The samples were measured after a conditioning time of 96 hours at 23 °C.

[0174] e) Comonomer content

[0175] Poly(propylene-co-ethylene)-ethylene content-IR spectrum

[0176] Quantitative infrared (IR) spectroscopy was used to quantify the ethylene content of poly(ethylene-co-propylene) copolymers by calibrating the primary method. 13 C solution state nuclear magnetic resonance (NMR) spectroscopy was determined, and calibration was facilitated by using a set of in-house non-commercial calibration standards of known ethylene content. The calibration procedure was performed in a conventional manner well documented in the literature. The calibration set consisted of 38 calibration standards with ethylene contents ranging from 0.2-75.0 wt% in pilot or full-scale production under various conditions. The calibration set was selected to reflect the typical copolymer species encountered in the final quantitative IR spectroscopy. Quantitative IR spectra were recorded in the solid state using a Bruker Vertex 70 FTIR spectrometer. Spectra were recorded on 25x25 mm square films with a thickness of 300 μm prepared by compression molding at 180-210°C and 4-6 MPa. For samples with very high ethylene content (>50 mol%), 100 μm thick films were used. Standard transmission FTIR spectroscopy was employed, which used a spectral range of 5000-500 cm -1 , aperture is 6mm, spectral resolution is 2cm -1 , 16 background scans, 16 spectral scans, interferogram zero filling factor of 64 and Blackmann-Harris 3-term apodization. Use the corresponding (CH2) >2 730 and 720cm of structural unit -1 (A Q ) to quantitatively analyze the total area of ​​CH2 rocking deformation at 762 and 694 cm -1 ). The quantitative band was compared with 4323 cm -1 (A R ) which corresponds to the CH building block (integration method G, limits 4650, 4007 cm -1). Then a secondary calibration curve was used to normalize the absorbance (A Q / A R ) predicts the ethylene content in weight percent. The calibration curve has been previously constructed by ordinary least squares (OLS) regression of the normalized absorbance and the main comonomer content measured on the calibration set.

[0177] Poly(propylene-co-ethylene)-ethylene content- 13 C NMR spectroscopy

[0178] for 1 H and 13 C, quantitatively recorded in solution using a Bruker Avance III400 NMR spectrometer operating at 400.15 and 100.62 MHz, respectively. 13 C{ 1 H} NMR spectra. All spectra were obtained using 13 C optimized 10 mm extended temperature probe was recorded at 125°C using nitrogen for all pneumatic devices. About 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) along with chromium (III) acetylacetonate (Cr(acac)3) to give a 65 mM solution of the relaxant in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475).

[0179] To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after initial sample preparation in a heating block. After insertion into the magnet, the tube was rotated at 10 Hz. This setting was chosen primarily for the high resolution and quantitative analysis required for accurate ethylene content quantification. Standard single pulse excitation was used in the absence of NOE, using an optimized tip angle, a 1 second recycle delay, and a two-stage WALTZ16 decoupling scheme (Zhou, Z. et al., J. Mag. Reson. 187 (2007) 225, and Busico, V. et al., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were obtained for each spectrum. For quantitative analysis, the NMR tube was rotated at 10 Hz after insertion into the magnet. The tube was rotated at 10 Hz after insertion into the magnet. This setting was chosen primarily for the high resolution and quantitative analysis required for accurate ethylene content quantification. Standard single pulse excitation was used in the absence of NOE, using an optimized tip angle, a 1 second recycle delay, and a two-stage WALTZ16 decoupling scheme (Zhou, Z. et al., J. Mag. Reson. 187 (2007) 225, and Busico, V. et al., Macromol. Rapid Commun. 2007, 28, 1128). 13 C{ 1H} NMR spectra are processed, integrated, and the relevant quantitative properties are determined from the integration. All chemical shifts are indirectly referenced to the central methylene of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This method allows for comparable references even if this structural unit is not present. Characteristic signals corresponding to ethylene incorporation are observed (Cheng, HN, Macromolecules 17 (1984), 1950), and the comonomer fraction is calculated as the fraction of ethylene in the polymer relative to all monomers in the polymer: fE = (E / (P+E). The method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) is used by 13 C{ 1 The comonomer fraction is quantified by integrating multiple signals over the entire spectral region in the H} spectrum. This method was chosen because of its robust properties and the ability to account for the presence of regional defects when necessary. The integration region is fine-tuned to increase applicability over the entire range of comonomer content encountered. For systems with very low ethylene content, where only isolated ethylene in the PPEPP sequence is observed, the method of Wang et al. is modified to reduce the impact of site integration that no longer exists. This method reduces the overestimation of the ethylene content of such systems and is achieved by reducing the number of sites used to determine the absolute ethylene content to E = 0.5 (Sββ + Sβγ + Sβδ + 0.5 (Sαβ + Sαγ)). By using this set of sites, using the same symbols in the article by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157), the corresponding integral equation becomes E = 0.5 (I H +I G +0.5(I C +I D )). The equation for absolute propylene content is not modified. The mole percent of comonomer incorporation is calculated from the mole fraction: E [mol %] = 100 * fE. The weight percent of comonomer incorporation is calculated from the mole fraction: E [weight %] = 100 * (fE * 28.06) / ((fE * 28.06) + ((1 - fE) * 42.08)).

[0180] f) PE, PS, PA, PET and TiO2 content

[0181] The film thickness method uses the strength of the dosing tape I(q) and the thickness of the pressed film T to determine the content using the following relationship: [I(q) / T]m+c=C, where m and c are obtained using the 13 The coefficients for determining the comonomer content were constructed from a calibration curve obtained from C-NMR spectroscopy.

[0182] Using a Nicolet Magna 550IR spectrometer with Nicolet Omnic FTIR software, the 13 The comonomer content was measured in a known manner by Fourier transform infrared spectroscopy (FTIR) calibrated with C-NMR. Films with a thickness of about 250 μ5 were compression molded from the samples. Similar films were made from calibration samples with known comonomer content. The comonomer content was determined by measuring the wavenumber range from 1430 to 1100 cm -1 The absorbance is measured as the peak height by selecting the so-called short baseline or the long baseline or both. The short baseline is drawn through the minimum point at about 1410 to 1320 cm -1 , and the long baseline is drawn at about 1410 to 1220 cm -1 A specific calibration is required for each baseline type. In addition, the comonomer content of the unknown samples is within the comonomer content range of the calibration samples.

[0183] g) Talc and chalk content

[0184] The TGA follows the following procedure:

[0185] Thermogravimetric analysis (TGA) experiments were performed using a Perkin Elmer TGA 8000. Approximately 10-20 mg of material was placed in a platinum pan. The temperature was equilibrated at 50°C for 10 minutes and then raised to 950°C at a heating rate of 20°C / min under nitrogen. The weight loss (WCO2) between approximately 550°C and 700°C was assigned to CO2 evolved from CaCO3, so the chalk content was estimated as:

[0186] Chalk content = 100 / 44 x WCO2

[0187] The temperature was then lowered to 300°C at a cooling rate of 20°C / min. The gas was then switched to oxygen and the temperature was raised again to 900°C. The weight loss in this step was designated as carbon black (Wcb). Knowing the contents of carbon black and chalk, the ash content excluding chalk and carbon black was calculated as:

[0188] Ash content = (ash residue) – 56 / 44 x WCO2 – Wcb

[0189] The ash content is the weight percentage measured at 900° C. in a first step carried out under nitrogen. The ash content is estimated to be the same as the talc content of the investigated recyclates.

[0190] h)MFR

[0191] The melt flow rate is measured at 230° C. and a load of 2.16 kg (MFR2). The melt flow rate is the number of grams of polymer which is extruded in 10 minutes by a test apparatus standardized to ISO 1133 at a temperature of 230° C. and a load of 2.16 kg.

[0192] i) Amount of metal

[0193] Determined by X-ray fluorescence (XRF).

[0194] j) Amount of paper and wood

[0195] Paper and wood were determined by conventional laboratory methods including grinding, flotation, microscopy and thermogravimetric analysis (TGA).

[0196] k) Limonene measurement

[0197] Limonene was quantified using solid phase microextraction (HS-SPME-GC-MS) by standard addition.

[0198] After adding different concentrations of limonene and a glass-coated magnetic stirring bar, 50 mg of ground sample was weighed into a 20 mL headspace vial. The vial was closed with a magnetic cap lined with silica gel / PTFE. A known concentration of diluted limonene standard was added to the sample using a microcapillary (10 pL). 0, 2, 20 and 100 ng of addition was equal to 0 mg / kg, 0.1 mg / kg, 1 mg / kg and 5 mg / kg limonene, in addition to a standard amount of 6.6 mg / kg, 11 mg / kg and 16.5 mg / kg limonene used in conjunction with some samples tested in this application. For quantification, ions 93 collected in SIM mode were used. Enrichment of the volatile fraction was performed by headspace solid phase microextraction using a 2 cm stable curved 50 / 30 pm DVB / Carboxen / PDMS fiber at 60 ° C for 20 minutes. Desorption was performed directly in the heated injection port of the GCMS system at 270 ° C.

[0199] GCMS parameters:

[0200] Column: 30m HP 5MS 0.25*0.25

[0201] Injector: Splitless, with 0.75 mm SPME liner, 270 °C

[0202] Temperature program: -10℃(1min)

[0203] Carrier gas: Helium 5.0, 31cm / s linear velocity, constant flow

[0204] MS: Single quadrupole, direct interface, 280°C interface temperature

[0205] Collection method: SIM scanning mode

[0206] Scan parameters: 20-300amu

[0207] SIM parameters: m / Z 93, 100 ms retention time

[0208] l) Total free fatty acid content

[0209] Fatty acid quantification was performed using headspace solid phase microextraction (HS-SPME-GC-MS) by standard addition.

[0210] 50 mg of ground sample was weighed in a 20 mL headspace vial and after adding different concentrations of limonene and a glass coated magnetic stir bar, the vial was closed with a silicone / PTFE lined magnetic cap. Diluted free fatty acid mixtures (acetic, propionic, butyric, valeric, hexanoic and octanoic acid) standards of known concentrations were added to the sample at three different levels using a 10 μL microcapillary. 0, 50, 100 and 500 ng additions were equivalent to 0 mg / kg, 1 mg / kg, 2 mg / kg and 10 mg / kg of each acid. Ion 60 collected in SIM mode was used for quantification of all acids except propionic acid, for which ion 74 was used.

[0211] GCMS parameters:

[0212] Column: 20m ZB Wax plus 0.25*0.25

[0213] Injector: Split 5:1, with glass-lined split liner, 250°C

[0214] Temperature program: 40℃(1min)@6℃ / min to 120℃, @15℃ to 245℃(5min)

[0215] Carrier gas: Helium 5.0, 40cm / s linear velocity, constant flow

[0216] MS: Single quadrupole, direct interface, 220°C interface temperature

[0217] Collection method: SIM scanning mode

[0218] Scan parameters: 46-250amu 6.6 scans / s

[0219] SIM parameters: m / z 60.74, 6.6 scans / s

[0220] m) Glass transition temperature

[0221] Determined by dynamic mechanical thermal analysis according to ISO 6721-7. Using TA Ares G2 testing equipment, on compression molded samples (40x10x1mm3 ) were measured in torsional deformation mode between -130°C and +160°C at a heating rate of 2°C / min and a frequency of 1 Hz.

[0222] experiment

[0223] Compatibilizers CE1 and IE1 to IE4 were prepared on a laboratory scale in a three-phase (bulk, gas phase 1 and gas phase 2) polymerization apparatus.

[0224] The catalyst used in the polymerization process of IE1-IE4 of the present invention and comparative example CE1 was prepared as follows:

[0225] Chemicals used:

[0226] 20% butylethylmagnesium (Mg(Bu)(Et), BEM) in toluene, provided by Chemtura; 2-ethylhexanol, provided by Amphochem; 3-butoxy-2-propanol-(DOWANOL TM PnB), provided by Dow; bis(2-ethylhexyl) citraconate, provided by SynphaBase; TiCl4, provided by Millenium Chemicals; toluene, provided by Aspokem; 1-254, provided by Evonik; heptane, provided by Chevron.

[0227] Preparation of Mg alkoxides:

[0228] A magnesium alkoxide solution was prepared by adding a mixture of 4.7 kg of 2-ethylhexanol and 1.2 kg of butoxypropanol to 11 kg of a 20 wt% solution of butylethylmagnesium (Mg(Bu)(Et)) in toluene in a 20 1 stainless steel reactor under stirring (70 rpm). During the addition, the reactor contents were kept below 45°C. After the addition was complete, the reaction mixture was mixed at 60°C (70 rpm) for 30 minutes. After cooling to room temperature, 2.3 kg g of donor bis(2-ethylhexyl) citraconate was added to the magnesium alkoxide solution, keeping the temperature below 25°C. Mixing was continued for 15 minutes under stirring (70 rpm).

[0229] Preparation of solid catalyst component:

[0230] 20.3 kg of TiCl4 and 1.1 kg of toluene were added to a 20 liter stainless steel reactor. Mixing at 350 rpm and keeping the temperature at 0°C, 14.5 kg of the Mg alkoxide prepared in Example 1 was added over 1.5 hours. 1.7 liters of 1-254 and 7.5 kg heptane, and mixed at 0 ° C for 1 hour, the temperature of the formed emulsion was raised to 90 ° C within 1 hour. After 30 minutes, the mixing was stopped, the catalyst droplets solidified and the formed catalyst particles were settled. After settling (1 hour), the supernatant was sucked off. The catalyst particles were then washed with 45 kg toluene at 90 ° C for 20 minutes, followed by two heptane washes (30 kg, 15 min). During the first heptane wash, the temperature dropped to 50 ° C, and during the second wash, the temperature dropped to room temperature.

[0231] The catalyst thus obtained was used together with triethylaluminium (TEAL) as cocatalyst and dicyclopentyldimethoxysilane (D-donor) as donor.

[0232] Virgin polymer powders (IE1-IE4 and CE1) or pellets (CE2-CE4) were compounded with recycled material pellets (Blend A#1, Blend A#2) in a co-rotating twin-screw extruder ZSK-18 Megalab at 220°C with 0.2 wt% Irganox B225 antioxidant and 0.05 wt% calcium stearate to produce compounds containing recycled material.

[0233] In comparative example CE2, SB815MO was used.

[0234] In comparative example CE3, ED007HP was used.

[0235] In comparative example CE4, SC876CF was used.

[0236] Commercial grade SB815MO is available from Borealis AG, Austria, and is a nucleated propylene-ethylene random heterophasic copolymer having an MFR of 1.5 g / 10 min, a melting temperature of 150° C., a total C2 content of 8.0 wt. %, and an XCS content of 28 wt. %.

[0237] Commercial grade ED007HP is available from Borealis AG, Austria, and is a nucleated propylene-ethylene heterophasic copolymer having an MFR of 5.5 g / 10 min, a melting temperature of 167° C., a total C2 content of 6.5 wt % and an XCS content of 25 wt %.

[0238] Commercial grade SC876CF is available from Borealis AG, Austria, and is a nucleated propylene-ethylene random heterophasic copolymer having an MFR of 3.8 g / 10 min, a melting temperature of 150° C., a total C2 content of 13.0 wt. %, and an XCS content of 43 wt. %.

[0239] Table 1 summarizes the method conditions and obtained characteristics.

[0240] Table 1. Preparation of compatibilizers

[0241] IE1 IE2 IE3 IE4 CE1 Reactor 1 Ontology Base only temperature [℃] 70 70 70 70 70 pressure [barg] 33.9 31.5 33.9 33.8 33.9 Retention time [h] 0.50 0.50 0.50 0.50 0.50 Shunt [weight%] 43.4 44.9 40.5 42.3 50.3 H2 / C3 [mol / kmol] 8.5 3.5 8.5 8.5 8.5 MFR [g / 10min] 90 25 90 90 90 XCS [weight%] 3.2 3.2 3.2 3.2 3.2 C2 [weight%] 0 0 0 0 0 Reactor 2 GPR1 temperature [℃] 80 80 80 80 80 pressure [barg] 25 25 25 25 25 Retention time [h] 0.74 0.58 0.66 0.64 0.78 Shunt [weight%] 41.8 40.5 44.2 42.6 49.7 C2 / C3 [mol / kmol] 121 99 108 101 103 H2 / C2 [mol / kmol] 266 321 309 336 330 H2 / C3 [mol / kmol] 32 32 33 34 34 MFR [g / 10min] 22 12 22 22 22 XCS [weight%] 16.5 16.5 16.5 16.5 16.5 C2 [weight%] 4.5 4.5 4.5 4.5 4.5 C2 / XCS [weight%] 17.3 17.3 17.3 17.3 17.3 IV / XCS [dl / g] 1.32 1.32 1.32 1.32 1.32 Reactor 3 GPR2 temperature [℃] 80 80 80 80 - pressure [barg] 14 25 25 14 - Retention time [h] 0.44 0.24 0.45 0.52 - Shunt [weight%] 14.9 14.6 15.3 15.1 - C2 / C3 [mol / kmol] 638 165 168 618 - H2 / C2 [mol / kmol] 5 25 0 0 - final Total MFR [g / 10min] 9.8 7.5 7.1 8.6 22.1 Total C2 [weight%] 11.1 7.3 8.2 11.1 4.5 XCS [weight%] 29.6 27.1 29.7 25.1 16.5 C2 / XCS [weight%] 26.8 21.1 21.7 28.4 17.3 IV / XCS [dl / g] 3.19 2.37 3.88 4.23 1.32

[0242] Table 2 shows the properties of the compatibilizers and compatibilizers used for comparison purposes.

[0243] Table 2: Properties of Compatibilizers and Comparative Compatibilizers

[0244]

[0245] Inventive Compatibilizer 1 has a moderately high IV (XCS) of 3.2 dl / g and a medium C2 (XCS) of 26.8 wt%. Inventive Compatibilizer 2 has a low IV (XCS) of 2.4 dl / g and a relatively low C2 (XCS) of 21.1 wt%. Inventive Compatibilizer 3 has a high IV (XCS) of 3.9 dl / g and a relatively low C2 (XCS) of 21.7 wt%. Inventive Compatibilizer 4 has a high IV (XCS) of 4.2 dl / g and a medium C2 (XCS) of 28.4 wt%. Comparative Compatibilizer 1 is a mixture of a propylene homopolymer and a random propylene ethylene copolymer. Comparative Compatibilizer 2 is a random heterophasic polypropylene copolymer with a low IV (XCS) of 2.0 dl / g and a low C2 (XCS) of 17.8 wt%. Comparative compatibilizer 3 is a heterophasic polypropylene copolymer with a high IV (XCS) of 6.8 dl / g and a medium C2 (XCS) of 28.0 wt%. Comparative compatibilizer 4 is a random heterophasic polypropylene copolymer with a low IV (XCS) of 1.8 dl / g and a medium C2 (XCS) of 28.7 wt%.

[0246] Table 3 shows the properties of the polypropylene / polyethylene blends (A) used for evaluation.

[0247] Table 3: Properties of polypropylene / polyethylene blend mixture (Blend A)

[0248]

[0249] Both blends showed unacceptable elongation at break properties.

[0250] Blend A#1 and Blend A#2 were mixed with the compatibilizer and comparative compatibilizer in different amounts as described above.

[0251] Table 4 shows the properties obtained for the compositions upgraded using Blend A#1.

[0252]

[0253] It can be seen that all compatibilizers according to the present invention increase the elongation at break to the desired value already at a surprisingly low amount of 5 wt%. At a higher compatibilizer loading of 30 wt%, this effect begins to disappear. The simply supported beam NIS (+23°C) benefits from the increase in compatibilizer loading, while the simply supported beam NIS (-20°C) is less dependent on the compatibilizer loading. The improvement in elongation at break can be achieved with a marginal degradation in stiffness of about 100 MPa. Compatibilizers 2, 3 and 4 of the present invention show a very significant increase (100 to 300%) in room temperature puncture resistance and especially low temperature puncture resistance at an ideal low loading of only 5%. At the ideal low compatibilizer loading, compatibilizers #3 and #4 of the present invention with relatively high IV (XCS) of 3.9 and 4.2 dl / g unexpectedly show the best balance of properties.

[0254] Table 5 shows the properties obtained for the compositions upgraded using Blend A#2.

[0255]

[0256] Surprisingly, when using the ideally small amount of 5 wt% compatibilizer, the tensile modulus is not negatively affected and is only affected by about 100 MPa at 15 wt% compatibilizer loading. At the same time, the elongation at break can be increased from 24% to at least 40%. At 5% compatibilizer loading, the Charpy NIS (+23°C) increases only marginally, while no change is observed in the Charpy NIS at 0°C. At higher compatibilizer loadings (15%), some significant Charpy NIS (+23°C) increases are observed (from 5.2 to 6.5-7.0 kJ / m 2 ) and some marginal increase in the simply supported beam at 0° C. The heat deformation temperature is not affected at 5% compatibilizer loading, while at 15% compatibilizer loading, the heat deformation temperature is greatly reduced from 87° C. to 83° C. It can be seen that the compatibilizers according to the present invention are alternative compatibilizers that can replace standard HECO and RAHECO (such as comparative compatibilizers CE3-Comp3 and CE4-Comp4).

Claims

1. Use of a compatibilizer (B) for upgrading a polypropylene-polyethylene blend (A), wherein the compatibilizer (B) is a multiphase copolymer comprising a matrix phase and an elastomeric phase dispersed therein, wherein the matrix phase comprises a polypropylene homopolymer-random polypropylene copolymer mixture, and wherein The heterophasic copolymer has the following properties: - a melt flow rate MFR2 of 2.0 to 30 g / 10 min, measured according to ISO 1133 at 2.16 kg load and 230°C, and - at least one melting point Tm1 in the range of 154°C to 168°C, - the second melting point Tm2 is in the range of 130°C to 160°C, - optionally a third melting point Tm3 in the range of 110°C to 125°C, - a xylene cold insoluble content (XCI) of 60 to 80% by weight, determined by cooling to 25°C according to ISO 16152, 1st edition, and - a xylene cold soluble content (XCS) of 20 to 40% by weight, determined by cooling to 25°C according to ISO 16152, 1st edition, wherein the xylene cold insoluble content (XCI) and the xylene cold soluble content (XCS) add up to 100% by weight, - the content of units derived from ethylene in the xylene cold insoluble fraction (XCI) is from 2.0 to 6.0% by weight, and - the content of units derived from ethylene in the xylene cold soluble fraction (XCS) is between 20.0 and 40.0% by weight; - the xylene cold soluble fraction (XCS) has an intrinsic viscosity of 2.1 dl / g to less than 6.0 dl / g when measured in decalin at 135°C according to DIN ISO 1628 / 1; The polypropylene-polyethylene blend (A) comprises (A-1) polypropylene, and (A-2) Polyethylene wherein the weight ratio of polypropylene (A-1) to polyethylene (A-2) is 19:1 to 1:19; The upgrade involves one or more of the following properties: (i) elongation at break measured according to ISO 527-2; (ii) Charpy notched impact strength measured at 23°C according to ISO 179-1eA; (iii) Charpy notched impact strength measured at 0°C according to ISO 179-1eA; (iv) Charpy notched impact strength measured at -20°C according to ISO 179-1eA; (v) puncture resistance measured at 23°C according to ISO 6603-2:2000; (vi) low temperature puncture resistance measured at 0°C or -20°C according to ISO6603-2:2000; The amount of the compatibilizer (B) used is 1 to 35 wt % relative to the final composition.

2. The method according to claim 1, wherein the xylene cold soluble fraction (XCS) determined by cooling to 25°C according to ISO 16152, first edition, has an intrinsic viscosity when measured in decalin at 135°C according to DIN ISO 1628 / 1 of 3.3 to 4.3 dl / g.

3. A method for upgrading a polypropylene-polyethylene blend (A), the polypropylene-polyethylene blend (A) comprising (A-1) polypropylene, and (A-2) Polyethylene wherein the weight ratio of polypropylene (A-1) to polyethylene (A-2) is 19:1 to 1:19; The upgrade involves one or more of the following properties: (i) elongation at break measured according to ISO 527-2; (ii) Charpy notched impact strength measured at 23°C according to ISO 179-1eA; (iii) Charpy notched impact strength measured at 0°C according to ISO 179-1eA; (iv) Charpy notched impact strength measured at -20°C according to ISO 179-1eA; (v) puncture resistance measured at 23°C according to ISO 6603-2:2000; (vi) low temperature puncture resistance measured at 0°C or -20°C according to ISO6603-2:2000; The method is achieved by melt blending the polypropylene-polyethylene blend (A) with a compatibilizer (B), The amount of the compatibilizer (B) is 1 to 35 wt % relative to the final composition, wherein the compatibilizer (B) is a heterophasic copolymer comprising a matrix phase and an elastomeric phase dispersed therein, wherein the matrix phase comprises a polypropylene homopolymer-random polypropylene copolymer mixture, and wherein The heterophasic copolymer has the following properties: - a melt flow rate MFR2 of 2.0 to 30 g / 10 min, measured according to ISO 1133 at 2.16 kg load and 230°C, and - at least one melting point Tm1 in the range of 154°C to 168°C, - the second melting point Tm2 is in the range of 130°C to 160°C, - optionally a third melting point Tm3 in the range of 110°C to 125°C, - a xylene cold insoluble content (XCI) of 60 to 80% by weight, determined by cooling to 25°C according to ISO 16152, 1st edition, and - a xylene cold soluble content (XCS) of 20 to 40% by weight, determined by cooling to 25°C according to ISO 16152, 1st edition, wherein the xylene cold insoluble content (XCI) and the xylene cold soluble content (XCS) add up to 100% by weight, - the content of units derived from ethylene in the xylene cold insoluble fraction (XCI) is from 2.0 to 6.0% by weight, and - the content of units derived from ethylene in the xylene cold soluble fraction (XCS) is between 20.0 and 40.0% by weight; - the xylene cold soluble fraction (XCS) has an intrinsic viscosity of 2.1 dl / g to less than 6.0 dl / g when measured in decalin at 135°C according to DIN ISO 1628 / 1.

4. The process according to claim 3, wherein the xylene cold soluble fraction (XCS) determined by cooling to 25°C according to ISO 16152, 1st edition, has an intrinsic viscosity when measured in decalin at 135°C according to DIN ISO 1628 / 1 of 3.3 to 4.3 dl / g.

5. A polypropylene-polyethylene composition, which can be obtained by blending the following materials: a) 65 to 99 wt.% of a polypropylene-polyethylene blend (A), the polypropylene-polyethylene blend (A) comprising A-1) Polypropylene, A-2) Polyethylene, The weight ratio of polypropylene to polyethylene is 19:1 to 1:

19. as well as b) 1 to 35 wt% of a compatibilizer (B), said compatibilizer (B) being a heterophasic copolymer comprising a matrix phase and an elastomeric phase dispersed therein, wherein said matrix phase comprises a polypropylene homopolymer-random polypropylene copolymer mixture, and wherein The heterophasic copolymer has the following properties: - a melt flow rate MFR2 of 2.0 to 30 g / 10 min, measured according to ISO 1133 at 2.16 kg load and 230°C, and - at least one melting point Tm1 in the range of 154°C to 168°C, - the second melting point Tm2 is in the range of 130°C to 160°C, - optionally a third melting point Tm3 in the range of 110°C to 125°C, - a xylene cold insoluble content (XCI) of 60 to 80% by weight, determined by cooling to 25°C according to ISO 16152, 1st edition, and - a xylene cold soluble content (XCS) of 20.0 to 40.0 wt. % as determined by cooling to 25°C according to ISO 16152, 1st edition, wherein the xylene cold insoluble content (XCI) and the xylene cold soluble content (XCS) add up to 100 wt. %, - the content of units derived from ethylene in the xylene cold insoluble fraction (XCI) is from 2.0 to 6.0% by weight, and - the content of units derived from ethylene in the xylene cold soluble fraction (XCS) is between 20.0 and 40.0% by weight; - the xylene cold soluble fraction (XCS) has an intrinsic viscosity of 2.0 dl / g to less than 6.0 dl / g when measured in decalin at 135°C according to DIN ISO 1628 / 1, and wherein the ratio of MFR2(blend (A)) / MFR2(compatibilizer (B)) measured according to ISO 1133 at 2.16 kg load and 230°C is in the range of 0.5 to 2.

0.

6. The polypropylene-polyethylene composition according to claim 5, wherein the xylene cold soluble fraction (XCS) determined according to ISO 16152, 1st edition, by cooling to 25°C has an intrinsic viscosity when measured in decalin at 135°C according to DIN ISO 1628 / 1 of 3.3 to 4.3 dl / g.

7. The polypropylene-polyethylene composition according to claim 5 or 6, wherein the compatibilizer (B) has a tensile modulus of at least 625 MPa measured according to ISO 527-2.

8. The polypropylene-polyethylene composition according to claim 5 or 6, wherein the polypropylene-polyethylene blend (A) has one or more of the following properties: (i) 0.1 ppm to 100 ppm limonene as determined by solid phase microextraction (HS-SPME-GC-MS); (ii) fatty acid content of 0.1 to 100 ppm as determined by solid phase microextraction (HS-SPME-GC-MS); (iii) a polyamide content of 0.05 to 1.5 weight percent as determined by NMR; (iv) a polystyrene content of 0.05 to 3.0 wt % as determined by NMR.

9. The polypropylene-polyethylene composition according to claim 5 or 6, having one or more of the following characteristics - a Charpy notched impact strength of at least 6.0 kJ / m² measured at 23°C according to ISO 179-1eA, and / or - a Charpy notched impact strength of at least 2.5 kJ / m² measured at -20°C according to ISO 179-1eA, and / or - an elongation at break of at least 300 % measured according to ISO 527-2, and / or - A tensile modulus of at least 800 mPa measured according to ISO 527-2.

10. The polypropylene-polyethylene composition according to claim 5 or 6, having the following properties: - a tensile modulus of at least 1200 MPa measured at 1 mm / min and 23°C according to ISO 527-2, and / or - The elongation at break measured according to ISO 527-2 is at least 40 %.

11. An article comprising the polypropylene-polyethylene composition according to any one of claims 5 to 10.

12. A multiphase copolymer comprising a matrix phase and an elastomeric phase dispersed therein, wherein the matrix phase comprises a polypropylene homopolymer-random polypropylene copolymer mixture, for compatibilization of polypropylene / polyethylene blends, wherein The heterophasic copolymer has the following properties: - a melt flow rate MFR2 of 2.0 to 30 g / 10 min, measured according to ISO 1133 at 2.16 kg load and 230°C, and - at least one melting point Tm1 in the range of 154°C to 168°C, - the second melting point Tm2 is in the range of 130°C to 160°C, - optionally a third melting point Tm3 in the range of 110°C to 125°C, - a xylene cold insoluble content (XCI) of 60 to 80% by weight, determined by cooling to 25°C according to ISO 16152, 1st edition, and - a xylene cold soluble content (XCS) of 20 to 40% by weight, determined by cooling to 25°C according to ISO 16152, 1st edition, wherein the xylene cold insoluble content (XCI) and the xylene cold soluble content (XCS) add up to 100% by weight, - the content of units derived from ethylene in the xylene cold insoluble fraction (XCI) is from 2.0 to 6.0% by weight, and - the content of units derived from ethylene in the xylene cold soluble fraction (XCS) is between 20.0 and 40.0% by weight; The xylene cold soluble fraction (XCS) has an intrinsic viscosity when measured in decalin at 135°C according to DIN ISO 1628 / 1 of 2.1 dl / g to less than 6.0 dl / g, and wherein optionally the heterophasic copolymer has a tensile modulus measured according to ISO 527-2 of at least 650 MPa.

13. The heterophasic copolymer according to claim 12, wherein the xylene cold soluble fraction (XCS) determined by cooling to 25°C according to ISO 16152, 1st edition, has an intrinsic viscosity when measured in decalin at 135°C according to DIN ISO 1628 / 1 of 3.3 to 4.3 dl / g.

14. The heterophasic copolymer according to claim 12 or 13, wherein the xylene cold soluble fraction (XCS) comprises units derived from ethylene and propylene only.

15. The heterophasic copolymer according to claim 12 or 13, wherein the heterophasic copolymer is a reactor blend of propylene homopolymer, random polypropylene copolymer and ethylene propylene rubber.

Citation Information

Patent Citations

  • Compositions obtained from recycled polyolefins

    WO2007071494A1

  • Polypropylene - polyethylene blends with improved properties

    WO2015169690A1

  • Upgraded recycled relatively polyethylene rich polyolefin materials

    WO2020070175A1

  • Upgraded recycled polypropylene rich polyolefin material

    WO2020070176A1